Mortality and morbidity of locally acquired hepatitis E in the national Scottish cohort: a multicentre retrospective study. Issue 10 (14th April 2020) - Wallace, Sebastian J.; Swann, Rachael; Donnelly, Mhairi; Kemp, Linda; Guaci, Julia; Murray, Aimee; Spoor, Johannes; Lin, Nan; Miller, Michael; Dalton, Harry R.; Hussaini, S. Hyder; Gunson, Rory; et al.
Summary: Background: Hepatitis E virus (HEV) is the most common acute viral hepatitis in Scotland. Little is known about the burden of morbidity and mortality, which can be high in chronic liver disease or immunocompromised states. Aims: To record the morbidity and mortality of HEV in Scotland. Methods: Demographic, clinical and laboratory data were collected retrospectively from all cases of HEV reported to virology departments across nine NHS health boards, between January 2013 and January 2018. Results: Five hundred and eleven cases were included (Mean age 62, 64% male). 58 (11%) cases had pre‐existing cirrhosis and 110 (21%) had diabetes. Three hundred and three patients required admission (59%), totalling 2747 inpatient bed days. Seventeen (3.3%) HEV‐related deaths were recorded. Factors that predicted mortality included haematological malignancy (OR 51.56, 95% CI 3.40‐782.83, P  = 0.005), cirrhosis (OR 41.85, 95% CI 2.85‐594.16, P  = 0.006), higher serum bilirubin (OR 1.01, 95% CI 1.01‐1.02, P  = 0.011) and chronic HEV infection (OR 0.02, 95% CI 0.02‐0.28, P  < 0.001). HEV infection affected 35 transplant patients of 106 total immunosuppressed patients (21%). Of these, 25 patients received Ribavirin therapy with a sustained virological remission of 76%. Thirty‐five (6.7%) patients developed acute or acute‐on‐chronic liver failure with two requiring transplant. Thirty‐seven (7.2%) patients reported neurological complications with 10 developing neuralgic amyotrophy, 6 Guillain‐Barré and 2 encephalitis. Forty‐four (8.6%) patients developed acute kidney injury. Conclusion: In Scotland, HEV causes a significant burden of inpatient admissions, organ failure and death. Cirrhosis and haematological malignancy are significant predictors of mortality. Neurological and renal complications occur in a significant minority.